Surface morphology of the developing respiratory epithelium of chicks - Othman, Fauziah; Purton, M. D.; Solomon, S. E. (Veterinary Association Malaysia, 2003)
The development of the respiratory tract of chicks between the age of I5-day-old embryos until 3-day-old chicks was carried out using scanning electron microscopy (SEM). The distribution of ciliated and microvillous cells was investigated, and given a score of 1 to 4 throughout the entire surface of the respiratory tract which include the middle nasal concha, larynx, cranial trachea, caudal trachea, intrapulmonary primary bronchus and secondary bronchus. The surface morphology of the intrapulmonary primary bronchus and secondary bronchus attained a mature densely ciliated epithelium as early as in the I5-day-old embryos. However, in the I9-to 20-day-old embryos, this was only found in the epithelium of the middle nasal concha, larynx, cranial and caudal trachea.